2012
DOI: 10.1080/01490400.2012.633847
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the Structure of Enduring Leisure Involvement

Abstract: (e.g., serious leisure, specialization, commitment) and their settings (e.g., sense of place, place identity).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 53 publications
(89 reference statements)
2
20
0
Order By: Relevance
“…Consistent with previous studies, we found that Attraction (i.e., importance of the leisure activity) was the highest-rated domain of enduring involvement (see Jun, Kyle, Absher, & Hammitt, 2008;Kyle, Graefe, Manning, & Bacon, 2003b;Kyle, Norman, Jodice, Graefe, & Marsinko, 2007;Vlachopolous, Theodorakis, & Kyle, 2008). Social Bonding was the second highest-rated domain of video gamers, which was similar to recreational anglers but differed from campers (Jun et al, 2008) and exercise enthusiasts (Vlachopolous et al, 2008). Social Bonding was followed by Attraction, and lastly Centrality.…”
Section: Enduring Involvementsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous studies, we found that Attraction (i.e., importance of the leisure activity) was the highest-rated domain of enduring involvement (see Jun, Kyle, Absher, & Hammitt, 2008;Kyle, Graefe, Manning, & Bacon, 2003b;Kyle, Norman, Jodice, Graefe, & Marsinko, 2007;Vlachopolous, Theodorakis, & Kyle, 2008). Social Bonding was the second highest-rated domain of video gamers, which was similar to recreational anglers but differed from campers (Jun et al, 2008) and exercise enthusiasts (Vlachopolous et al, 2008). Social Bonding was followed by Attraction, and lastly Centrality.…”
Section: Enduring Involvementsupporting
confidence: 89%
“…Social Bonding was followed by Attraction, and lastly Centrality. This is not surprising as Centrality is generally the lowest-rated domain in most enduring involvement studies (Jun et al, 2008;Kyle et al, 2003b).…”
Section: Enduring Involvementmentioning
confidence: 89%
“…Jun et al 2012). For example, Chen et al (2013) only measure the relationship between leisure motivation and leisure satisfaction in a structural equation model without modelling the actual decision.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“… Enduring involvement has been extensively researched in relation to consumer behavior and applied to leisure experiences (Havitz & Dimanche, 1990;Jun, Kyle & Vlachopoulos, 2012;Kyle & Chick, 2002;Lee & Scott, 2009;McIntyre,1989) but had merited only a footnote in the SLP literature (Stebbins, 2007, p.23, n.5), until a recent discussion of 'the seriousness dimension of involvement' (Stebbins, 2014, p.32-34).…”
Section: Theory Content: Complementarymentioning
confidence: 99%